Long-term potentiation is impaired in CD200-deficient mice: a role for Toll-like receptor activation. - LYNCH, MARINA; COSTELLO, DEREK; COX, FRANCES FIONNUALA; BROWNE, TARA; DENIEFFE, STEPHAINE; LYONS, ANTHONY (My University, 2011)
The membrane glycoprotein CD200 is expressed on several cell types including neurons whereas expression of its receptor, CD200R, is restricted principally to cells of the myeloid lineage, including microglia. The interaction between CD200 and CD200R maintains microglia and macrophages in a quiescent state, therefore CD200-deficient mice express an inflammatory phenotype exhibiting increased macrophage or microglial activation in models of arthritis, encephalitis and uveoretinitis. Here, we report that lipopolysaccharide (LPS) and Pam3CysSerLys4 (Pam3Csk4) exerted more profound effects on release of the proinflammatory cytokines, interleukin (IL)-1?, IL-6 and tumour necrosis factor (TNF)-? in glia prepared from CD200-/-, compared with wildtype, mice. This effect is explained by the loss of CD200 on astrocytes which modulates microglial activation. Expression of Toll-like receptors (TLR)-4 and -2 was increased in glia prepared from CD200-/- mice and the evidence indicates that microglial activation, assessed by the increased numbers of CD11b+ cells which stained positively for both MHCII and CD40, was enhanced in CD200-/-, compared with wildtype, mice. These neuroinflammatory changes were associated with impaired long-term potentiation (LTP) in CA1 of hippocampal slices prepared from CD200-/- mice. One possible explanation for this is the increase in TNF? in hippocampal tissue prepared from CD200-/- mice, since TNF? application inhibited LTP in CA1. Significantly, LPS and Pam3Csk4, at concentrations which did not affect LTP in wildtype mice, inhibited LTP in slices prepared from CD200-/- mice, likely due to the accompanying increase in TLR2 and TLR4. Thus the neuroinflammatory changes which result from CD200 deficiency have a negative impact on synaptic plasticity.
PUBLISHED
Keywords: Neuroscience; Immunology; Infection; Toll-like receptors; Genes & Society; Immunology, Inflammation & Infection